Cellular Uptake and Computational Analysis of [131I]-Xanthine and [131I]-Hypoxanthine in Human Prostate Cancer Cell Line (LNCaP) - Wongso, Hendris; Mahendra, Isa; Setiadi, Yanuar; Rattyananda, Badra Sanditya; Rizaludin, Asep; Pranisuari, Ni Made Yuktikamura Galih; Kusumaningrum, Crhisterra Ellen (UI Scholars Hub, 2024)
Potent radiolabelled compounds eligible for therapy of prostate cancer need to be developed. Hence, we developed two candidate therapeutic agents bearing the iodine-131 (131I) radionuclide, namely, [131I]-xanthine (3,7-dihydropurine-2,6-dione) and [131I]-hypoxanthine (1,9-dihydro-6H-purin-6-one). The radiolabelled compounds were subjected to a cellular uptake study, which was accomplished by incubating [131I]-xanthine and [131I]-hypoxanthine with the human prostate cancer cell line (LNCaP) for 5, 15, 30, 60, and 90 min. Results showed that the accumulation of both [131I]-xanthine and [131I]-hypoxanthine in prostate cancer cells was significantly higher than the control group (131I). [131I]-xanthine rapidly accumulated in prostate cancer cells, with the highest percentage of cellular uptake of 2.73% ± 0.40% observed at 30 min of incubation. By contrast, [131I]-hypoxanthine exhibited more efficient accumulation in prostate cancer cells, especially at 60 and 90 min of incubation, with cellular uptake values of 11.5% ± 3.14% and 11.9% ± 1.83%, respectively. Furthermore, the computational analysis showed that radioiodinated xanthine and hypoxanthine provide potential binding affinities and interaction on both androgen and prostate-specific membrane antigen receptors. Overall, this study indicates that [131I]-xanthine and [131I]-hypoxanthine can be potentially developed as therapeutic agents for prostate cancer.